Review of Jwarahara Gutika Yogas Containing Vatsanabha in Sahasrayogam - KV Reshma Phalgunan; Madavi Subhashchandra (International Journal of Ayurveda and Pharma Research, 2021)
Vatsanabha is Vishavarga dravya mentioned in many of the Ayurveda Samhitas, which is commonly used in Ayurvedic medicinal preparations. It has a property of Jwarahara, Amaghna, Swedajana which is very useful in Jwara cases. The drugs like Parada, Gandhaka, Hingula along with Vatsanabha shows fast action on Jwara. In Ayurveda there are many formulations mentioned with Jwarahara properties. In this article we are studying about 17 Jwarahara Gutika yogas containing Vatsanabha which are mentioned in Sahasrayogam. Purpose of this study is to analyse these Yoga in the aspect of their ingredients, Bhavana dravya, Anupana, Sevana vidhi, and their role in management of Jwara. When we analysing each and every ingredients on these Yogas there are certain similarities in ingredients, Bhavana dravya, Anupana of these medicines. Most of these ingredients have Deepana Pachana karma, Katu Thikta rasa, Ushna veerya, Katu vipaka etc which are beneficial for Samprapti vighatana of Jwara. As Sahasrayogam is a compilation of popular formulations which are commonly used by ancient physicians of Kerala, it is assumed that all of this Yoga were once in practice. These formulations are to be kept in tablet form which is very convenient for their administration, palatability etc. But very few of them are available in market. In this current scenario of Covid pandemic Ayurveda field should rethink about these potent medicines of Jwara for the well being of our community, and further study and clinical trial also needed to know their action on Jwara.